2012
DOI: 10.1080/07373937.2012.705205
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption in the Convective Drying of Timber Analyzed by a Multiscale Computational Model

Abstract: Energy consumption during timber drying has become an increasingly important issue, alongside conventional concerns such as quality, cost, and drying time. This paper proposes a detailed analysis of the energy consumption evolution in conventional kiln drying using a sophisticated modelling approach. The formulation of energy consumption proposed by Perré et al. [1] was embedded in a multiscale computational model to consider kiln drying of a stack of boards. The drying of each board in the stack is simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Thus, mass and energy balances were written in terms of the rate of dry air, which allows one to ignore the effect of air density due to the temperature and the relative humidity. [41] The environmental and heated air properties were determined by a psychrometric chart considering the altitude of São José do Rio Preto, Brazil (498 m).…”
Section: Energy Balancementioning
confidence: 99%
“…Thus, mass and energy balances were written in terms of the rate of dry air, which allows one to ignore the effect of air density due to the temperature and the relative humidity. [41] The environmental and heated air properties were determined by a psychrometric chart considering the altitude of São José do Rio Preto, Brazil (498 m).…”
Section: Energy Balancementioning
confidence: 99%
“…Polge and Keller (1973), Klumpers (1994), Guilley (2000), Natterer et al (2004), andPerré et al (2012) showed that density decreases when the cambium is aging. R e f e r e n c e s Aussenac G. (1993) EW -vessel diameter in early wood, LW -vessel diameter in latewood, VD -vessel density, N -number of vessels, L -vessel length, INZ -internal zone, EXZ -external zone, SD -standard deviation, CV -coefficient of variation, S -significant difference, NS -non-significant difference…”
Section: Discussionmentioning
confidence: 99%
“…(i) For the importance of the vessel lumen and vessel number in the external zone and in the internal zone according to Hacke et al (2001), Meinzer (2003), Bucci et al (2004), andPerré et al (2012) suitable indicators are water storage capacity and conducting efficiency of water in the stem of Q. ilex. The surface of the lumen is 0.12 mm 2 in the internal zone, and 0.28 mm 2 in the external zone.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the multiscale models for drying has been conducted on timber. A series of works has been published for the various length scales for timber (Perré, Rémond, & Turner, ; Perré, Rémond, Colin, Mougel, & Almeida, ). Readers are directed to Perré () for a breakdown of the homogenization and an in‐depth description of the transport which occurs in these studies.…”
Section: Multiscale Modeling Frameworkmentioning
confidence: 99%